Konseling Individu dengan Teknik Thought Stopping dalam Mengatasi Perilaku Agresif - Dwi Rahmawati; Suryati Suryati; Zhila Jannati (Scidacplus, 2023)
Aggressive behavior can cause conflicts, fights, acts of violence and also make relationships with other people worse. This study aims to determine the description of aggressive behavior on client N at the Ar Rahman Drug Rehabilitation Center. This research uses a qualitative approach and case study method. Data collection techniques in this study are observation, interviews and communication. Data analysis techniques in this study are pattern matching, explanation and time series analysis. The subjects of this study were client